A low cost fractal CPW fed antenna for UWB applications with a circular radiating patch - Akram El Hamdouni; Abdelali Tajmouati; Jamal Zbitou; Hamid Bennis; Ahmed Errkik; Larbi El Abdellaoui; Mohamed Latrach (Universitas Ahmad Dahlan, 2020)
In this study a validated antenna into simulation and through measurement has been described and analyzed. The coplanar waveguide (CPW) technique has been chosen to feed the radiating patch while the two ground planes have been partially designed in the top side of the substrate. The fractal geometry, applied to the circular radiator, has been obtained by merging the circular and rectangular shapes. The fiberglass FR-4, with a single side of 35μm copper thickness, has been used to achieve the antenna material with a permittivity of 4.4, a thickness of 1.6 mm, a loss tangent of 0.025 and an overall dimension of 34x43 mm2. The proposed CPW fractal antenna has been configured to operate in the frequency range 3.1-10.6 GHz published by the federal communications commission (FCC) as an ultra-wide band (UWB). To calculate the return loss, the gain, the current density and the radiation pattern of the simulated antenna, two electromagnetic solvers have been involved which are the CST microwave studio and ADS. The series of measurement have been performed by using the network analyzer and the anechoic chamber in order to confirm the computed antenna.